Does consumption of nitrate-containing beetroot juice affect anaerobic performance in athletes? - Greisman, G. J. (Bastyr University, 2020)
Objectives: Nitrates in beetroot juice (BR) are a precursor of nitric oxide (NO). NO, a vasodilator, may improve muscle efficiency. This study measured effects of a BR supplement on 500-meter (500m) row, countermovement jump (CMJ) and blood lactate in CrossFit athletes. Past studies analyzed effects of BR on young male athletes; this study included male and female middle-aged athletes. Methods: Study was randomized, cross-over, double-blind, placebo-controlled design. Thirty athletes age 18-60 consumed either BR (6.5 mmol nitrate) or nitrate-free beetroot juice placebo (PL) and rowed 500m two hours later. After a seven-day washout period, athletes repeated row with either BR or PL for comparison. Lactate and CMJ were measured pre and post-row. Results: Ten males age 44.0 ± 14.0 and twenty females age 43.5 ± 8.5, participated. The 500m row times ranged from 88.2 to 150.7 seconds(s). Although 60% of all participants rowed faster with BR (mean 112.8s), compared to PL (mean 113.4s), difference in means of row times (-0.56) was not significant overall (p = 0.29). For males, row times were significantly faster (1,0s difference, p = 0.04) with BR compared to PL. For females, difference in mean row time (-0.34s) was not significant (p = 0.66). Competitive rowers were defined as those who rowed under 110s (N=15). Competitive rowers (10 M, 5 F) times were significantly faster with BR compared to PL (difference in means -0.9s, P = 0.009, but there was a significant interaction effect of drink order (group) and drink [F( 1,1) = 7.89, p=0.015]. No difference in lactate and CMJ values were noted. Conclusion: Overall, anaerobic performance did not significantly improve with BR compared to PL. This study uniquely tested a population of middle-aged, primarily female, CrossFit athletes.